Pathological regression patterns following neoadjuvant chemo-immunotherapy in head and neck squamous cell carcinoma: a pilot study - Wang, Dikan; Zeng, Fanning; Zhang, Sien; Hu, Wanming; Wang, Yahui; Ouyang, Daiqiao; Zeng, Bin; Zeng, Guozhong; Li, Jingyuan; Liao, Guiqing; Liang, Yujie (Frontiers in Immunology, 2025)
IntroductionNeoadjuvant chemoimmunotherapy (NACI) has drawn considerable attention in Head and neck squamous cell carcinoma (HNSCC) owing to its potential in functional preservation and treatment-failure reduction. Yet whether the surgical extent can be narrowed following NACI is largely debatable due to a potential non-centripetal tumor regression may result in scattered microfoci residing beyond the narrowed margin.MethodsIn this pilot study, we characterized the tumor regression pattern in a post-NACI HNSCC cohort using a whole-mount histopathological approach. The MRI examinations before and after NACI were used to evaluate the objective response rate (ORR).ResultsOf the 52 patients enrolled, the ORR was 75%. Pathological complete response (pCR) rate was 15.4%, and the major pathological response (MPR) rate was 40.4%. Two major regression patterns were identified in whole-mount tumor sections, centripetal regression and non-centripetal regression. Centripetal regression was observed in 37 patients (71.2%) and was subcategorized into complete regression (Ia, 15.4%), unifocal centripetal regression (Ib, 36.5%), and multifocal centripetal regression (Ic, 19.2%). Non-centripetal regression was seen in 15 patients (28.8%) and was subcategorized into scattered regression (IIa, 25.0%) and non-regression (IIb, 3.8%). Moreover, we found a pre-NACI CPS higher than 20 or post-NACI (18)F-FDG SUVmax reduction exceeding 50% were potential predictive factors for the centripetal regression pattern.DiscussionWe revealed for that centripetal regression was the predominant pattern of regression after NACI in HNSCC. Hence, our data presumably supports a reduced surgical extent in post-NACI HNSCC patients. Future studies should focus on identifying accurate predictive factors for the regression pattern, which may eventually assist in risk stratification and surgical decision making.ConclusionsThe pattern of tumor pathological regression after NACI for HNSCC is mainly divided into centripetal and non-centripetal regression, with the former accounting for the major portion of the regression.